Suppression of higher-order modes in a large-optical-cavity waveguide structure for high-power high-efficiency 976-nm diode lasers. (May 2019) - Zhou, Kun; Du, Weichuan; Li, Yi; Kang, Junjie; Zhang, Liang; Hu, Yao; Tan, Hao; Wang, Zhao; Gao, Songxin; Wu, Deyong; Tang, Chun
Abstract: High-power high-efficiency broad-area diode lasers are highly efficient light sources. A study on the design of large-optical-cavity 976-nm diode lasers is presented here. Efforts were made to suppress the higher-order modes and to explore new design methods for high-power high-efficiency diode lasers. The mode distribution, confinement factor, internal optical loss and far-field pattern were numerically calculated to analyze the waveguide design. To suppress the higher-order transverse modes, both gain and loss discrimination mechanisms were experimentally investigated. By adjusting the position of the active region, successful suppression of higher-order modes can be achieved. Alternatively, higher-order modes can be suppressed by increasing the cavity length, which is attributed to the discrimination of modal loss between the higher-order modes and the fundamental mode. A high-efficiency 4-mm-long broad-area single emitter with an ultralow internal optical loss of 0.27 cm–1 and an internal quantum efficiency of 93.5% was designed and fabricated. A high slope efficiency of 1.1 W/A and >66% wall-plug efficiency was obtained at 25 °C under continuous current injection. The far-field divergence angles with 95% power content were 38° and 9.7° for the fast and slow axes, respectively, at an output power of 10.0 W. Highlights: The design of high-power laser diode with large-optical-cavity is presented. Fundamental modal gain controlled by quantum well confinement factor is a key parameter for the suppression of higher-order modes. The modal propagation loss depend on the cavity length can be used as another parameters to suppress the higher-order modes. 4-mm-long cavity devices shows a high wall-plug efficiency of >66% and low far-field divergence angle of 38° for the fast axes.